Localization of the human female breast in primary somatosensory cortex - Rothemund, Yvonne; Schaefer, Michael; Grüsser, Sabine M.; Flor, Herta (Experimental brain research, 2005)
Rationale: Despite an extensive body of research on the topography of the primary somatosensory cortex (S1) little is known about the representation of the trunk. Aim: The aim of this study was to determine the representation of the breast in S1 in human females. Results: The representation of the human breast in primary somatosensory cortex was determined in ten healthy female subjects. Non-painful electrical stimulation of the mammilla (Th4 dermatome), groin (L1 dermatome) and the first digit of both sides of the body activated cutaneous receptors and thus elicited somatosensory evoked potentials. The representation of these body parts in primary somatosensory cortex (S1) was determined using neuroelectric source imaging. Equivalent current dipole localizations were overlaid with individual structural magnetic resonance images to account for individual cortical differences. The breast representation was localized between the representation of the groin and the first digit. In the medial-lateral direction the representation of the breast was approximately 15 mm lateral of the longitudinal fissure in the contralateral hemisphere. Source localizations were stable across subjects. However, one subject showed ipsilateral representation of the breast, which might be related to bilateral receptive fields of the ventral body midline representation. This study confirms the Penfield and Rasmussen (1950) invasive data by use of noninvasive source imaging.
Gesehen am 04.11.2020